Correlation between smartphone thermographic temperature and visual infusion phlebitis score in surgical patients with peripheral intravenous access at Dr. Hasan Sadikin General Hospital - Teguh Marfen Djajakusumah; Rani Septrina; Hiskia Pangeran (Institute of Accounting Research and Novation (IARN), 2026)
Phlebitis is a common complication of peripheral intravenous catheter use that increases patient morbidity and length of hospital stay. The Visual Infusion Phlebitis (VIP) score is widely used for clinical assessment but remains subjective and does not incorporate temperature as an inflammatory marker. Smartphone-based infrared thermography offers a potential objective, non-invasive, and practical adjunct parameter. This study aimed to determine the correlation between local temperature measured by smartphone thermography and VIP score in patients with peripheral intravenous access at Dr. Hasan Sadikin General Hospital. An observational analytic study with a cross-sectional design was conducted in 37 patients with catheter dwell time ≥72 hours. Temperature at the infusion site was measured using a smartphone-based thermal camera and compared with the contralateral healthy area, while phlebitis severity was simultaneously assessed using the VIP score. Data were analyzed using the Shapiro–Wilk normality test and Spearman correlation test at a 95% confidence level. The mean VIP score was 1.86 ± 1.38 (range 0–4), and the mean infusion-site temperature was 35.9 ± 1.7°C (range 33.2–38.1°C). A statistically significant, moderate positive correlation was found between VIP score and thermographic temperature (r = 0.52; p = 0.002), indicating that higher VIP scores were associated with increased local temperature, reflecting the underlying inflammatory process. These findings suggest that smartphone-based thermographic imaging may serve as a useful objective adjunct in phlebitis evaluation among patients with peripheral intravenous access, complementing rather than replacing comprehensive clinical assessment.